PENGEMBANGAN E-LKPD BERBASIS CASE BASED LEARNING PADA MATERI PERUBAHAN LINGKUNGAN UNTUK MELATIHKAN SIKAP SADAR LINGKUNGAN SISWA KELAS X DI SMAN 2 NGANJUK - Riyanto, Ain Noor Ismu; Rachmadiarti, Fida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students’ low environmental awareness is due to their lack of participation in environmental conservation. The results of observations regarding environmental awareness in 10th grade classes at SMAN 2 Nganjuk also support the issue of low environmental awareness at the high school level. Therefore, this study aims to develop an E-LKPD based on Case-Based Learning (CBL) on the topic of environmental change to foster environmentally conscious attitudes among 10th grade high school students, which is appropriate from both theoretical and practical perspectives. This development research, using the ADDIE model, produced an E-LKPD equipped with features containing learning activities based on CBL syntax to foster environmental awareness. The E-LKPD was declared theoretically feasible through expert validation with a validity score of 3.9 (highly valid). The E-LKPD was then tested on a limited basis on 36-grade X students at SMAN 2 Nganjuk. As a result, the E-LKPD was declared practical based on the results of the response questionnaire, with a score of 94.3% (highly practical). Thus, the CBL-based E-LKPD on environmental change is declared feasible for use in fostering environmental awareness among students.